Adolescents' understanding of observation, prediction, and hypothesis in everyday and educational contexts. - Cortéz, Ramón; Niaz, Mansoor (Journal of Genetic Psychology, 1999)
A study was conducted to examine adolescents' understanding of the science-related categories of “observation,” “prediction,” and “hypothesis” in everyday and educational contexts. Subjects were 688 adolescents aged between 11 and 17 years, who were tested using the Test of Hypothetico-Deductive Reasoning developed by the writers. The subjects were required to classify statements from everyday and educational contexts according to the three categories. Findings revealed that the subjects performed increasingly better from Grade 6 to Grade 11 on both the everyday and educational context items. In general, however, the subjects had considerable difficulty in classifying the statements: the 11th-grade subjects, who produced the best performance, had a mean score of 47.6 percent on everyday items and a mean score of 37.3 percent on educational context items. Thus, despite some recent contrasting findings, school curricula should include development of students' hypothetico-deductive reasoning abilities.